Commedia Togata: the Terenzio of Goldoni and the contest for literary authority - Leigh, M (Springer, 2008)
This paper examines the competition for authority between two mid-18th century Italian comic poets - Carlo Goldini and Pietro Chiari - and the importance of this appeal to classical authority. Concentrating on the Moliere and Terenzio of Goldoni and on the Plauto of Chiari, but also paying close attention to the contribution of contemporary literary pamphleteers, the author endeavours to show how Goldoni consistently identifies himself with the great reformers of the comic theatre. The effect of the Terenzio is to oblige Chiari to take on the role of the modern Plautus, even though this necessarily contradicts all that his admirers have said of him in their panegyric 'Sulla vera poesia teatrale'.